Guidelines for the diagnosis and management of asthma by the Polish Society of Allergology, Polish Society of Lung Diseases, Polish Society of Pediatric Pneumology, and Polish Society of Family Medicine (STAN4T) - Rafał Pawliczak; Andrzej Emeryk; Adam Barczyk; Paweł Majak; Maciej Kupczyk; Joanna Chorostowska-Wynimko; Piotr Kuna; Paweł Śliwiński; Anna Bręborowicz; Zbigniew Doniec; Henryk Mazurek; Agnieszka Mastalerz-Migas; et al. (Alergologia Polska)
The updated and enhanced guidelines for the diagnosis and treatment of asthma in children and adults were developed by expert physicians from four Polish medical societies, using the GRADE methodology. The guidelines provide a concise and clear overview of the principles of asthma diagnosis and treatment, designed for physicians of all medical specialties, with a particular focus on primary care physicians. They can also be used in coordinated care processes.